2015
DOI: 10.1136/jmedgenet-2014-102882
|View full text |Cite
|
Sign up to set email alerts
|

ACASQ1founder mutation in three Italian families with protein aggregate myopathy and hyperCKaemia

Abstract: We show, by Sanger and exome sequencing, that the protein aggregate myopathy with benign evolution and muscle inclusions composed of excess CASQ1, affecting three Italian families, is due to the D244G heterozygous missense mutation in the CASQ1 gene. Investigation of microsatellite markers revealed a common haplotype in the three families indicating consanguinity and a founder effect. Results from immunocytochemistry, electron microscopy, biochemistry and transfected cell line investigations contribute to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 36 publications
2
23
5
Order By: Relevance
“…Proteases can be used at low concentrations to distinguish folded from unfolded proteins, based on the observation that unfolded proteins are cut more rapidly than structured proteins due to the inability of proteases to access buried sites. To investigate CASQ1 proteins conformation/aggregation at increasing Ca 2+ concentrations, recombinant CASQ1 proteins containing the three different TAM mutations were purified from bacteria together with the WT and the p.Asp244Gly previously reported in vacuolar aggregate myopathy (Di Blasi et al., ; Rossi et al., ). CASQ1 aggregation propensity was analyzed by limited trypsin proteolysis in absence or presence of increasing Ca 2+ concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteases can be used at low concentrations to distinguish folded from unfolded proteins, based on the observation that unfolded proteins are cut more rapidly than structured proteins due to the inability of proteases to access buried sites. To investigate CASQ1 proteins conformation/aggregation at increasing Ca 2+ concentrations, recombinant CASQ1 proteins containing the three different TAM mutations were purified from bacteria together with the WT and the p.Asp244Gly previously reported in vacuolar aggregate myopathy (Di Blasi et al., ; Rossi et al., ). CASQ1 aggregation propensity was analyzed by limited trypsin proteolysis in absence or presence of increasing Ca 2+ concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…P values ≤0.05 and 0.005 are indicated by * and **, respectively. Experiments were repeated three times proteins conformation/aggregation at increasing Ca 2+ concentrations, recombinant CASQ1 proteins containing the three different TAM mutations were purified from bacteria together with the WT and the p.Asp244Gly previously reported in vacuolar aggregate myopathy (Di Blasi et al, 2015;Rossi et al, 2014b). CASQ1 aggregation propensity was analyzed by limited trypsin proteolysis in absence or presence of increasing Ca 2+ concentrations.…”
Section: Pasp44asn and Pgly103asp Proteins Are More Susceptible To mentioning
confidence: 99%
“…The main clinical features of these patients were myalgia, muscle cramps or mild muscle weakness, and mild to moderate elevation of serum CK. Recently, a heterozygous missense mutation in the CASQ1 gene, involving an evolutionarily-conserved residue of the CASQ1 protein (p.D244G), has been identified [ 3 , 4 ]. Nevertheless, the pathophysiological mechanisms related to this mutation remain mostly unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two years, two reports have appeared linking one mutation in CASQ1 to vacuolar aggregate myopathy [35,73]. Patients carrying the heterozygous CASQ1 p.D244G mutation, affecting a residue that lies within the Ca 2+ binding domain of calsequestrin 1, have a mild myopathy, suffer from muscle cramps, elevated CK levels, reduced muscle strength and fatigue.…”
Section: Casq1 Mutations and Vacuolar Aggregate Myopathymentioning
confidence: 99%
“…Patients carrying the heterozygous CASQ1 p.D244G mutation, affecting a residue that lies within the Ca 2+ binding domain of calsequestrin 1, have a mild myopathy, suffer from muscle cramps, elevated CK levels, reduced muscle strength and fatigue. From a functional point of view, muscle fibers isolated from these patients show (i) decreased Ca 2+ release following caffeine administration, (ii) increased glycogen content and misoriented SR junctions, (iii) an increase by approximately 25% of calsequestrin 1 content and (iv) a lower content of polymerized calsequestin [35,73]. Interestingly a report on the physicochemical properties of wild type and p.D244G mutated CASQ1 showed that the mutation reduces the Ca 2+ binding properties of calsequestrin 1 and causes it to form large aggregates in vitro [36].…”
Section: Casq1 Mutations and Vacuolar Aggregate Myopathymentioning
confidence: 99%